1 / 11

Software Verification 1 Deductive Verification

Software Verification 1 Deductive Verification. Prof. Dr. Holger Schlingloff Institut für Informatik der Humboldt Universität und Fraunhofer Institut für Rechnerarchitektur und Softwaretechnik. Hoare calculus. ⊢ { [v:=t] } v=t {  } (ass) ⊢ {  } skip {  } (usually omitted)

dex
Download Presentation

Software Verification 1 Deductive Verification

An Image/Link below is provided (as is) to download presentation Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author. Content is provided to you AS IS for your information and personal use only. Download presentation by click this link. While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server. During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

Presentation Transcript


  1. Software Verification 1Deductive Verification Prof. Dr. Holger Schlingloff Institut für Informatik der Humboldt Universität und Fraunhofer Institut für Rechnerarchitektur und Softwaretechnik

  2. Hoare calculus • ⊢ {[v:=t]} v=t {} (ass) • ⊢ {} skip {} (usually omitted) • if ⊢ {}1{}and ⊢ {} 2{}, then {} {1; 2}{} (seq) • if ⊢ {  b} 1{} and ⊢ {  ¬b} 2{}, then ⊢ {}if (b) 1 else 2 {} (ite) • if ⊢ {  b} {}, then ⊢ {}while (b) {  ¬b} (whi) • If ⊢ (’  ) and ⊢ {} {}, then ⊢ {’}  {} (imp1) • If ⊢ {}  {} and ⊢ (  ’), then ⊢ {}  {’} (imp2) • the semantics (meaning) of a program  is the set of all derivable Hoare-tripels {} {}

  3. Examples • {x==17} x++ {x==18} • {x==17} y=x+1 {y==18} • {x==17} {x++; y=x+1} {y==19} • {a==m  b==n}if (a<=b) c = a else c = b{c==min(m,n)} • {a==m>0  b==n>0} while (a!=0) {c = a; a = b%a; b = c} {b==gcd(m,n)}

  4. Sample proof: exponentiation Consider the following while-program  {c==1; while(b!=0){ if (b%2==0){b=b/2; a=a*a} else {b=b-1; c=c*a} } } We want to show that ⊢ {a==m  b==n}  {c==m**n}

  5. Sample proof: exponentiation (1) ⊢ {a==m  b==n} c=1 {a==m  b==n  c==1} (ass) (2) ⊢ {a==m  b==n} c=1 {c*a**b==m**n} (imp,1) (3) ⊢ {c*(a*a)**(b/2)==m**n} b=b/2 {c*(a*a)**b==m**n} (ass) (4) ⊢ {c*a**b==m**n} b=b/2 {c*(a*a)**b==m**n} (3,imp) (5) ⊢ {c*(a*a)**b==m**n} a=a*a {c*a**b==m**n} (ass) (6) ⊢ {c*a**b==m**n} {b=b/2; a=a*a} {c*a**b==m**n} (seq,4,5) (7) ⊢ {c*a*a**(b-1)==m**n} b==b-1 {c*a*a**b==m**n} (ass) (8) ⊢ {c*a**b==m**n} b==b-1 {c*a*a**b==m**n} (7,imp) (9) ⊢ {c*a*a**b==m**n} c==c*a {c*a**b==m**n} (ass) (10) ⊢ {c*a**b==m**n} {b==b-1; c==c*a} {c*a**b==m**n} (seq,8,9) (11) ⊢ {c*a**b==m**n  b%2==0} {b=b/2; a=a*a} {c*a**b==m**n} (6,imp) (12) ⊢ {c*a**b==m**n  b%2!=0} {b==b-1; c==c*a} {c*a**b==m**n} (10,imp)

  6. Sample proof: exponentiation (2) ⊢ {a==m  b==n} c=1 {c*a**b==m**n} (imp,1) (11) ⊢ {c*a**b==m**n  b%2==0} {b=b/2; a=a*a} {c*a**b==m**n} (12) ⊢ {c*a**b==m**n  b%2!=0} {b==b-1; c==c*a} {c*a**b==m**n} (13) ⊢ {c*a**b==m**n} if(b%2==0) {b=b/2; a=a*a} else {b==b-1; c==c*a} {c*a**b==m**n} (ite,11,12) (14) ⊢ {c*a**b==m**n  b!=0} if ... {c*a**b==m**n} (imp,13) (15) ⊢ {c*a**b==m**n} while (b!=0) if ... {c*a**b==m**n  b==0} (whi,14) (16) ⊢ {a==m  b==n} {c=1; while (b!=0) if ...} {c*a**b==m**n  b==0} (seq,2,15) (17) ⊢ {a==m  b==n}  {c==m**n} (imp,16)

  7. Other notation • else { • {c*a**b=m**n  b!=0  b%2!=0} • b=b-1; • {c*a*a**b=m**n } • c=c*a • {c*a**b=m**n } • } • {c*a**b=m**n } • } • {c*a**b=m**n  b==0} • } • {c==m**n} {a==m  b==n} {c==1; {a==m  b==n  c==1} {c*a**b=m**n} while(b!=0){ {c*a**b=m**n  b!=0} if (b%2==0){ {c*a**b=m**n  b!=0  b%2==0} b=b/2; {c*(a*a)**b=m**n} a=a*a {c*a**b=m**n} } {c*a**b=m**n}

  8. A more complex example: gcd {a==m>0  b==n>0} while (a!=b) if (a>b) a=a-b else b=b-a {a==b==gcd(m,n)} where a==gcd(m,n) iff a|m  a|n  x (x|m  x|n ⇒ x<=a) What we need to know from math is (x < y)  gcd (x, y) == gcd (x, y − x) (x > y)  gcd (x, y) == gcd (x, x − y) (x == y)  gcd (x, y) == x

  9. show gcd(x,y)==gcd(x,y−x) (x < y)  gcd (x, y) == gcd (x, y − x) If x<y, then y-x>0, hence gcd(x,y-x) is well-defined. If z|x and z|y then z|(y-x): x=z*x’, y=z*y’  y-x=z*(y’-x’) If z|x and z|(y-x) then z|y: x=z*x’, (y-x)=z*(y-x)’  x+(y-x)=y=z*(x’+(y-x)’) Hence {z: z|x  z|y} == {z: z|x  z|(y-x)} Which means gcd (x, y) == gcd (x, y − x)

  10. Hoare proof for gcd {a==m>0  b==n>0} {gcd(a,b)==gcd(m,n)} while (a!=b) {gcd(a,b)==gcd(m,n)  a!=b} if (a>b) {gcd(a,b)==gcd(m,n)a>ba!=b} {gcd(a-b,b)==gcd(m,n)} a=a-b {gcd(a,b)==gcd(m,n)} else • {gcd(a,b)==gcd(m,n)a<=ba!=b} {gcd(a,b-a)==gcd(m,n)} b=b-a {gcd(a,b)==gcd(m,n)} {gcd(a,b)==gcd(m,n)} {a==b  gcd(a,b)==gcd(m,n)} {a==b==gcd(m,n)}

  11. gcd, Alternative Version {a==m>0  b==n>0} while (a!=0) {c = a; a = b%a; b = c} {b==gcd(m,n)} Proof: homework!

More Related